2005
DOI: 10.1038/sj.npp.1300927
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Dose Methadone Maintenance on Cocaine Place Conditioning, Cocaine Self-Administration, and Mu-Opioid Receptor mRNA Expression in the Rat Brain

Abstract: Methadone maintenance at appropriate doses can effectively reduce cocaine abuse in heroin-dependent individuals. In the present studies, we investigated the effect of high-dose methadone maintenance cocaine conditioned place preference (CPP) and cocaine intravenous self-administration. Rats implanted with methadone-filled osmotic mini-pumps (20 and 55 mg/kg/day, SC) and conditioned with cocaine (1, 5, and 20 mg/kg, i.p.) did not express cocaine CPP. Similarly, rats implanted with methadone pumps (55 mg/kg/day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 72 publications
9
52
0
Order By: Relevance
“…In fact, during cocaine self-administration on a PR (Experiment 2), it was found that rats maintained on 30 mg/kg/day methadone failed to adjust to the increased work requirement to obtain drug infusions and, as a result, obtained significantly less cocaine than control animals. These results are consistent with previous findings from our laboratories showing that rats maintained on doses of methadone above 20 mg/kg/day do not respond for cocaine-conditioned cues, do not approach a cocaine-conditioned environment, and do not show reinstatement of cocaine seeking after priming injections of cocaine (Leri et al, 2004(Leri et al, , 2005(Leri et al, , 2006. It is important to note that methadone-induced blockade of cocaine seeking observed in our experiments is not an artifact of impaired sensory-motor functioning.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In fact, during cocaine self-administration on a PR (Experiment 2), it was found that rats maintained on 30 mg/kg/day methadone failed to adjust to the increased work requirement to obtain drug infusions and, as a result, obtained significantly less cocaine than control animals. These results are consistent with previous findings from our laboratories showing that rats maintained on doses of methadone above 20 mg/kg/day do not respond for cocaine-conditioned cues, do not approach a cocaine-conditioned environment, and do not show reinstatement of cocaine seeking after priming injections of cocaine (Leri et al, 2004(Leri et al, , 2005(Leri et al, , 2006. It is important to note that methadone-induced blockade of cocaine seeking observed in our experiments is not an artifact of impaired sensory-motor functioning.…”
Section: Discussionsupporting
confidence: 93%
“…The same dose of cocaine has been used in previous experiments employing Sprague-Dawley male rats to investigate the effect of methadone maintenance on cocaine self-administration on a continuous schedule of reinforcement and on cocaine-seeking behavior (Leri et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the present study, we found that amygdalar MOP-r mRNA levels were not affected by either chronic heroin or heroin withdrawal (data not shown). Therefore, further time-course studies are necessary before alternative explanations, such as indirect amygdalar activation due to extra-amygdalar opioid action can be ruled out (eg, in the nucleus accumbens core during opiate or cocaine withdrawal) (Yao et al, 2005;Leri et al, 2006;Zhou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%